Upaya Peningkatan Mutu Pendidikan Madrasah di Era Digital - Yasmansyah, Yasmansyah; Zakir, Supratman (Indonesian Research Journal on Education, 2022)
This study aims to determine the efforts to improve the quality of madrasa education in the digital era. Madrasa education in the digital era has brought changes in various aspects of people's lives, including education. Various kinds of challenges, advantages and disadvantages in the implementation of the teaching and learning process become the thoughts of teachers and education stakeholders to be able to participate in realizing national education goals. The research method used is a literature review method related to the transformation of education in the digital ear with various studies sourced from references from books, journal articles and other sources that support this paper. The results show that improving the quality of education is a top priority in all educational institutions including madrasas, to achieve quality education, efforts can be made by planning curriculum, improving the quality of teachers/educators, costs and infrastructure to produce the best graduates who can face educational challenges. in the digital era and accepted by society.